2016
DOI: 10.18849/ve.v1i2.33
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Factors Influencing Thigh Circumference Measurement in Dogs

Abstract: Objective: To evaluate inter-and intra-observer variability, influence of hair clipping and laser guidance on canine thigh circumference (TC) measurements amongst observers.Background: It was our goal to further study the reliability of canine TC measurements as currently performed. For this purpose we designed a cadaveric model that allows for controlled inflation of the thigh resembling increase of muscle mass. We also investigated the impact of novel technologies (laser guidance) and hair clipping on TC mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 26 publications
2
12
0
Order By: Relevance
“…Smith et al found significant inter- and intra-observer variability when measuring thigh circumference midway between the hip and stifle in Labrador Retrievers (13). Similar findings were found by Bascuñán et al in a two phase cadaveric and clinical study measuring thigh circumference at the 50% TL (8). This contrasts with our findings, where there was significant reliability between observers following training at both the 50 and 70% TL in the extended stifle position groups.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Smith et al found significant inter- and intra-observer variability when measuring thigh circumference midway between the hip and stifle in Labrador Retrievers (13). Similar findings were found by Bascuñán et al in a two phase cadaveric and clinical study measuring thigh circumference at the 50% TL (8). This contrasts with our findings, where there was significant reliability between observers following training at both the 50 and 70% TL in the extended stifle position groups.…”
Section: Discussionsupporting
confidence: 89%
“…Placing the hind limb in an extended stifle position may have less variability and result in more consistent measurements of thigh girth. Measurements made in standing dogs in one study resulted in low agreement among investigators and may be due to the variations in the standing stifle angle and differences in muscle tension while standing (8). There is evidence from previous studies that maintaining the stifle in a standing position may result in unacceptable variability (8, 13).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations